The Effect of Corporate Governance Practices on Financial Structure in Emerging Markets: Evidence from BRICK Countries and Lessons for Turkey - Aras, Guler (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
In this article, I aim to investigate major emerging markets (BRICK [Brazil, Russia, India, China, South Korea] countries and Turkey) in terms of governance practices, which differ in many ways including board structures, board procedures, disclosures, audit committee meeting frequency, ownership structures, and minority shareholder rights. Moreover, I aim to relate these governance practices to the impact they have on financial structures in terms of financial profitability and financial leverage. Findings provide support for the notion that board independence, representation of women on the board, duality, and the number of board meetings are key factors in determining corporate governance efficiency and play important roles in enhancing firm financial structure in BRICK firms. I also attempt to identify the main issue in corporate governance research, which is whether governance practices are universal or instead depend on country and firm characteristics. These multicountry results, together with the view of common- and civil-law differentiation, suggest that country characteristics strongly influence the aspects of governance practices while predicting firm financial structure.
Keywords: BRICK; corporate governance; financial leverage; financial profitability; panel data; FIRM PERFORMANCE; OWNERSHIP STRUCTURE; BOARD SIZE; AGENCY COSTS; CEO DUALITY; CHINA; MECHANISMS; VALUATION; COMPANIES; Business & Economics; International Relations